Assistance to improve occupational safety and health behavior in traditional diver fishing communities - Ibrahim, Hasbi; Lagu, Abdul Majid HR.; Syahrir, Sukfitrianty; Nildawati, Nildawati (SAMATA JOURNAL OF PUBLIC HEALTH SCIENCE, 2025)
Traditional fishermen are exposed to various occupational hazards due to the nature of their work, often lacking adequate safety practices and health knowledge. This community service initiative aimed to improve occupational safety and health (OSH) behaviors among traditional fishermen on Kambuno Island, Pulau Sembilan District, Indonesia. Using a one-group pre- and post-test design, the intervention targeted a sample of 60 out of 862 local fishermen. The program involved counseling sessions and the distribution of OSH guidelines specifically tailored for fishing activities, delivered over a two-month period. The intervention assessed various components related to OSH, including the use and completeness of Personal Protective Equipment (PPE), knowledge and practice levels, personal health habits, treatment-seeking behavior, and environmental health awareness. Results showed significant improvements in PPE usage, knowledge levels, and OSH practices. For instance, post-intervention data indicated a substantial increase in the use of head, hand, and foot protection, as well as life vests. Furthermore, positive behavioral changes were observed in boat cleaning, self-care, and formal healthcare-seeking behaviors, as fishermen increasingly opted for health centers over traditional treatments. The findings suggest that focused OSH interventions can effectively enhance safety and health behaviors in high-risk fishing communities. This program underscores the importance of continued education and monitoring to sustain these improvements and reduce occupational risks in traditional fishing communities.